Measurements of methane emissions by gas chromatography and photo acoustic gas monitor - Trong Nghia, Hoang (2017)
The Climate Food and Farming (CLIFF) Research Network is an international research network that helps to expand young researchers' knowledge and experience working on climate change mitigation in smallholder farming. CLIFF provides grants for selected doctoral students to work with CGIAR researchers affiliated with the Standard Assessment of Mitigation Potential and Livelihoods in Smallholder Systems (SAMPLES) project. This presentation is "Measurements of methane emissions by gas chromatography and photo acoustic gas monitor" by Hoang Trong Nghia, a CLIFF student with CCAFS Low Emission Development.